2015
DOI: 10.1111/ajt.12964
|View full text |Cite
|
Sign up to set email alerts
|

FR104, an Antagonist Anti-CD28 Monovalent Fab’ Antibody, Prevents Alloimmunization and Allows Calcineurin Inhibitor Minimization in Nonhuman Primate Renal Allograft

Abstract: These authors contributed equally to the senior authorship of this study.Selective targeting of CD28 might represent an effective immunomodulation strategy by preventing T cell costimulation, while favoring coinhibition since inhibitory signals transmitted through CTLA-4; PD-L1 and B7 would not be affected. We previously showed in vitro and in vivo that anti-CD28 antagonists suppress effector T cells while enhancing regulatory T cell (Treg) suppression and immune tolerance. Here, we evaluate FR104, a novel ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 68 publications
3
60
1
Order By: Relevance
“…response to tuberculin; 3) peripheral regulatory T cell induction or accumulation was excluded in blood because we did not observe significant modulation of regulatory T cell numbers or frequencies, and elimination of these cells did not modify the ex vivo IFN-g response to tuberculin after treatment with FR104 as compared with control; and 4) we and others have previously reported that selective CD28 blockade induced regulatory T cell infiltrates at the site of inflammation (15,17,18,23). In this study, we did not observe important T cell infiltrates in skin biopsies after selective CD28 blockade, suggesting that if regulatory T cells directly control effector T cell activation, they would preferably be located in draining lymph nodes.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…response to tuberculin; 3) peripheral regulatory T cell induction or accumulation was excluded in blood because we did not observe significant modulation of regulatory T cell numbers or frequencies, and elimination of these cells did not modify the ex vivo IFN-g response to tuberculin after treatment with FR104 as compared with control; and 4) we and others have previously reported that selective CD28 blockade induced regulatory T cell infiltrates at the site of inflammation (15,17,18,23). In this study, we did not observe important T cell infiltrates in skin biopsies after selective CD28 blockade, suggesting that if regulatory T cells directly control effector T cell activation, they would preferably be located in draining lymph nodes.…”
Section: Discussionmentioning
confidence: 86%
“…We assessed the efficiency of selective CD28 blockade in a nonhuman primate skin inflammatory model on the control of cellular and humoral memory responses and the effect on latent viral infections. It had been shown previously that CD28 blockade induces immune regulation and prevents allograft rejection or autoimmune attacks in rodents (14) and nonhuman primate (15,23,24) models. However, in these models, animals were immunologically naive toward immunizing Ags.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have examined the impact of selective CD28 blockers in both mouse and NHP models of transplantation and autoimmunity (32)(33)(34)(35)(36)(37). For example, FR104, an antagonist anti-CD28 monovalent Fab' antibody, has been shown to prevent alloimmunization and prolong graft survival (38,39). These effects were CTLA-4 dependent and involved the promotion of Foxp3 + regulatory T cell responses following transplantation (36,40).…”
Section: Introductionmentioning
confidence: 99%